EVALUATION OF ANDESITE SLOPES STABILITY USING ROCK MASS CLASSIFICATION AND LIMIT EQUILIBRIUM METHOD IN THE AREA OF GUNUNG BATU AND GRAHA PUSPA, WEST BANDUNG REGENCY, WEST JAVA - Cakrabuana, Wira
The fact that West Java has a high susceptibility to landslides, potential earthquake hazards due to fault activity, and is the province with the highest population in Indonesia encourages research on the potential for earthquake-induced landslides at that location. A study was conducted to determine the stability of andesite slopes in the Gunung Batu and Graha Puspa areas, West Bandung Regency, using rock mass classification and limit equilibrium method. The data used include rock property test results, rock thin section description results, references to regional seismicity, rock hardness survey results, scanline survey results, and drone photos. The methods used include literature studies (on geology and regional seismicity, data acquisition and processing techniques, as well as analysis and evaluation techniques), secondary data search (rock property test results and rock thin section description results), rock hardness survey, scanline survey, drone photo taking, rock mass classification using Rock Mass Rating (RMR), discontinuity kinematic analysis, analysis of earthquake contribution, slope stability analysis using Slope Mass Rating (SMR) (empirical) and limit equilibrium methods (deterministic), as well as evaluation of slope stability. Andesite slopes in Gunung Batu and Graha Puspa have RMR values of 74-81, which are included in the category of good-very good rock mass. The design parameters and engineering properties that can be applied to andesite slopes at both sites are as follows: rock mass cohesion of 0.3-0.4 to >0.4 MPa, rock mass internal friction angle of 35-45 to >45°, and safe cut slope of 65 to >70°. Slopes GB-01, GB-02, GB-03, GP-02, and GP-03 have the potential for toppling failure, while slope GP-01 has the potential for wedge failure. Andesite slopes in Gunung Batu and Graha Puspa have SMR values of 72-96, which are included in class I-II. Slopes with this category have characteristics stable-very stable, have the potential of block failure to no failure, and the probability of failure is 0.2-0. Almost no major reinforcement is required. Several minor reinforcement options can be applied, such as scaling, toe ditch, fence, and spot bolting. Slope GP-02 cannot be modeled for stability because it has a very low discontinuity dip (rejected by the toppling failure software system). In factual conditions (dry-static), all slopes in Gunung Batu and Graha Puspa are in stable condition (factor of safety (FoS) ? 1.1). In general, all slopes experience an increase in FoS value when slopes are varied under conditions in order: saturated-pseudostatic, saturated-static, dry-pseudostatic, and dry-static; except for slope GB-03 (because the slope’s FoS is not sensitive to changes in kh and %w). The extreme increase in FoS on slopes GB-01 and GP-03 is due to the discontinuity configuration favorable to slope stability. In Gunung Batu, slope GB-02 is stable in all variations of moisture conditions, slope GB-01 is unstable at %w = 100 with kh ? 0.08 g, and slope GB-03 was unstable in all variations of moisture conditions with kh ? 0.175 g (%w = 0), 0.15 g (%w = 50), and 0.05 g (%w = 100). Slope GB-02 is stable in all variations of seismicity conditions, slope GB-03 is completely unstable at kh = 0.15 g and 0.3 g, as well as slope GB-01 is unstable at the same conditions with %w ? 92 (kh = 0.15 g) and 70 (kh = 0.3 g). In Graha Puspa, slope GP-01 is completely unstable at %w = 100, slope GP-03 is unstable at the same condition with kh ? 0.09 g. Slope GP-01 was unstable in all variations of seismicity conditions with %w ? 93 (kh = 0 g), 80 (kh = 0.15 g), and 60 (kh = 0.3 g), while slope GP-03 was unstable at kh = 0.15 g (%w ? 88) and kh = 0.3 g (%w ? 58).